Divine epithets in the Ugaritic alphabetic texts - Rahmouni, Aicha. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2008)
This volume comprises an analysis of 112 divine epithets occurring in the alphabetic cuneiform texts from Ras Shamra and Ras Ibn Hani. It is intended to encompass all the epithets of the individual Ugaritic deities, semi-divine, and demonic beings, both good and evil, attested in the published texts. The epithets are profound expressions of the religious views of the ancient Ugaritians and their comprehension is essential for understanding the role, character, and status of the various deities in the Ugaritic pantheon. Particular attention has been paid to parallel divine epithets in Akkadian, biblical Hebrew, and classical Arabic.